A Conjectured Cournot Duopoly Model for the EU–US Automobile Trade: A Game Theoretic Analysis of the TTIP’s Most Traded Product - Kovács, Eszter (Competitio, 2021)
Economic actors, in their interactions with each other, certainly make decisions which are able to improve their original situation. In the case of free trade agreements, tariffs have the effect to manipulate countries’ trade and welfare. In this paper, we try to estimate the impacts of the Transatlantic Trade and Investment Partnership (TTIP) on the profit level of participating countries in the context of the Cournot duopoly model. More specifically, we elaborate the most traded product (MTP) and determine the profit levels in the equilibrium regarding two scenarios (pre and post situations of the TTIP). The findings suggest that the Cournot model seems suitable since it illustrates the possible options and provides a guideline for the decision-making process. Based on the model, it can be shown at which point the highest benefit can be achieved for the participating economies (EU, US) i.e. how long it is worth for the parties to apply additional automotive tariffs.